2004
DOI: 10.1016/j.cogpsych.2003.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A model for evidence accumulation in the lexical decision task

Abstract: We present a new model for lexical decision, REM-LD, that is based on REM theory (e.g., ). REM-LD uses a principled (i.e., Bayes' rule) decision process that simultaneously considers the diagnosticity of the evidence for the 'WORD' response and the 'NONWORD' response. The model calculates the odds ratio that the presented stimulus is a word or a nonword by averaging likelihood ratios for lexical entries from a small neighborhood of similar words. We report two experiments that used a signal-to-respond paradigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 71 publications
(124 reference statements)
9
93
1
Order By: Relevance
“…It has sometimes been argued that lexical decision can be performed before semantic access (e.g., Forster, 1976;Morton, 1969) or that lexical decision does not necessarily require semantic information (Plaut, 1997). Other theories have given semantic activation a central role in word recognition (Balota et al, 1991;Norris, 2006;Wagenmakers et al, 2004). The present results suggest that one source of variability in observed semantic effects in lexical decision could be individual differences.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…It has sometimes been argued that lexical decision can be performed before semantic access (e.g., Forster, 1976;Morton, 1969) or that lexical decision does not necessarily require semantic information (Plaut, 1997). Other theories have given semantic activation a central role in word recognition (Balota et al, 1991;Norris, 2006;Wagenmakers et al, 2004). The present results suggest that one source of variability in observed semantic effects in lexical decision could be individual differences.…”
Section: Discussionmentioning
confidence: 49%
“…There are now a number of models of the visual word recognition system (e.g., Coltheart, Rastle, Perry, Langdon & Ziegler, 2001;Harm & Seidenberg, 2004;Norris, 2006;Wagenmakers et al, 2004), and these assume that visual word recognition involves extraction of three kinds of information about word stimuli: orthography (spelling), phonology (sound), and semantics (meaning). The task that is most commonly used to study the word recognition system is the lexical decision task (LDT; i.e., is the stimulus a real word?…”
mentioning
confidence: 99%
“…Thus, how a study item is encoded-which features are used and what their values are-depends on the participant's prior knowledge stored in semantic memory. Access to semantic memory depends not only on the physical features of the stimulus, such as the letters of a word, but can also affected by context, as has been found in studies of lexical decision and naming (Wagenmakers et al, 2004). Finally, although we do not model it here, just as semantic memory is used to determine the features encoded in an episodic trace, the episode augments the knowledge stored in semantic memory (Nelson & Shiffrin, 2013).…”
Section: V(t)mentioning
confidence: 99%
“…In particular, robust context effects have been observed in lexical decision tasks in which participants classify strings of letters as words (e.g., CAT) or nonwords (e.g., CXT; see, e.g., Glanzer & Ehrenreich, 1979;Gordon, 1983;Grainger & Jacobs, 1996;Ratcliff, Gomez, & McKoon, 2004). Wagenmakers et al (2004) also identified a mirror effect in lexical decision. They observed improved performance for both words and nonwords (a mirror effect) when the similarity of the nonwords to the words was decreased.…”
Section: Experiments 1-4mentioning
confidence: 99%